Effect of Month and Season of Calving on Milk Yield Per Kg Live Body Weight in Murrah Buffaloes under Organized Farm Conditions (Indian Journal of Animal Production and Management, 2024)
The present study was conducted using 23  years of data pertaining to 1223 lactations of Murrah  buffaloes under the suckling system of calf rearing  at Cattle and Buffalo Farm (Livestock Production  and Management Section), ICAR-Indian Veterinary  Research Institute, Izatnagar (Bareilly), Uttar  Pradesh, India. The milk yields per kg of live body  weight (MY/BW) were estimated by dividing  monthly milk yields (MMY) in lactation by respective  average monthly live body weights (MLB) of milch  buffaloes during 1-13th months of lactation. The  effect of the season of calving was studied by  considering five seasons i.e. Winter (December February), Spring (March-April), Summer (May June), Rainy (July-September), and Autumn  (October-November) and months of caving  considered were 1st to 12th months in a year.  Season and months of calving showed significant to  highly significant differences (P≤0.01/0.05) for milk  yields per kg live body weights for most of the  months in lactations in Murrah buffaloes.
Keywords: calving month; calving season; milk yield per kg live body weight; Murrah buffalo